Large-bore central venous catheters for the collection of peripheral blood stem cells - Hahn, Uwe; Goldschmidt, Hartmut; Salwender, Hans; Haas, Rainer; Hunstein, Werner (Journal of clinical apheresis, 1995)
In order to establish a peripheral blood stem cell graft, repeated aphereses are necessary in the majority of patients. Each apheresis requires withdrawal and reinfusion of blood with high flow rates. To guarantee these flow rates, large-bore catheters are needed for central venous access. Subcutaneously tunneled silicone catheters (Hickman) caused venous thrombosis in 10-40% of the patients. We therefore used polyurethane large-bore catheters only for the time of peripheral blood stem cells (PBSC) collection. Via a Seldinger guidewire following delineation of the right (160 patients) or left (23 patients) internal jugular vein by ultrasound, 183 apheresis catheters have been inserted when the white blood cell count was >1.0 × 109/L and a measurable population of CD34+ cells was detected by fluorescence-activated cell sorter analysis. The median flow rate was 70 ml/min (range 50-80 ml/min). We observed the following complications: puncture of the carotid artery in 2%, pneumothorax in 0.5%, local infection in 3%, and catheter-related septicemia in only 2% of the patients. At the time of the removal of the catheters, we detected thrombosis of the internal jugular vein in 5% of the patients by ultrasound. The collection of PBSC with short-term, large-bore catheters is effective and is associated with a low incidence of infection and thrombosis.
Elektronische Reproduktion der Druck-Ausgabe 14. November 2006
Gesehen am 15.05.2025